Peran Tata Usaha Dalam Pengelolaan Arsip Sekolah di Sekolah SMP Swasta Al-Jihad Medan - M Iqbal; Lucky Milan Sari; Ali Asmul; Rahmansyah Marbun (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In essence, dministration  is  carrying  out  administrative   work  related  to writing sor collecting  data, incluiding  financial  and  other  matters within a company. Archive control with planning  for  making,  maintaning  services  for  those  who  need  archives, then  selecting  records  that need  to  be  destroyed  or  preserved. What  is  the  focus  of   this  research  is  the   role of administration in the management of school Al-jihad Medan Middle School, Kec, Medan Tembung, Medan  City, North  Sumatra.  As  for  the  purpose  of   this  study  is  to  find  out  how  the administrative staff in managing records. This type of research is descriptive qualitative, namely a research   procedure  that  produces  descriptive  data  in  the  form  the  observed  people  and  actors, directed  from  the  individual  as  a  whole  without  isolating   individuals  and  organizations  in variables  but  viewing  them  as  part  of  the  needs.  In  data  collecting  tehniques  in  this  study, various  tehniques were used, namely interviews, observations and  documentation. Based on observations  made by  researchers  at the private  junior hig school Al-jihad Medan MTs level in indrakasih,Kec, Medan Tembung, Medan City, North Sumatra, it can be seen that there are several problems,  first,  how  to  manage records  that  are  still  inefective, second,  archives  that  are  not  in accordance  with  school year. Thirdly  the  arrangement  of   the  school  archives  which  is  still  not neat, as well as regarding the spatial  administration  which  is  still  mixed  with  some  honorary  teachers. Fourth,  inadeguate facilities and infrastructure for archive storage.